Hydrothermal vent temperatures track magmatic inflation and forecast eruptions at the East Pacific Rise, 9°50’N - Thibaut Barreyre; Jean-Arthur Olive; Daniel J. Fornari; Jill M. McDermott; Ross Parnell-Turner; Kim Moutard; Jyun-Nai Wu; Milena Marjanović (Proceedings of the National Academy of Sciences, 2025)
Hydrothermal vent temperatures fluctuate in response to transient magmatic and tectonic activity at the axis of mid-ocean ridges (MORs) and modulate energy fluxes from the deep Earth to the ocean. Such fluctuations have thus far only been documented on time scales of minutes to years, because of the scarcity of long, continuous observations. Here, we assemble a ~35-year-long time series of exit fluid temperatures from five hydrothermal vents on the East Pacific Rise axis, between 9°46’-51’N. This dataset reveals a steady increase in maximum venting temperatures atop the central part of the axial magma lens (AML), from ~350 °C to ~390 °C between the 1991–92 and 2005–06 eruptions. Temperatures decreased back to ~350 °C shortly after the 2005–06 eruption and have been rising ever since. We interpret the temperature increase as a result of a steady decrease in upflow zone permeability caused by the steady inflation of the AML compressing the oceanic upper crust. Using laboratory-determined pressure–permeability relations, we estimate crustal pressurization rates of 0.38 MPa/y (1992–2005) and 0.33 MPa/y (post-2006), consistent with geodetic observations from 2009–2011. Decadal fluctuations in hydrothermal vent temperatures likely mimic the rate of AML pressurization, yielding valuable new constraints on the dynamics of magmatic replenishment and eruptions at MORs. Notably, this temperature time series underpinned our forecast of the April 2025 eruption at the study site.